THE DECISION OF MINIMAX PROBLEMS IN THE NON-UNIFORM ENVIRONMENT OF SELECTIVELY WORKING DEVICES THE MODIFIED ALGORITHM ALEXEEVA - D.G. KRASNIY (Advanced Engineering Research)
The present considered work modification of algorithm Alekseev for reception of the approached decision of a minimax problem of the theory of schedules is considered to system with selectivity of computing units. Keywords: the theory of schedules, a problem of planning, list of algorithm Alekseev.